Racial discrimination and life satisfaction among Black Canadians: the mediating role of social support and the moderating roles of gender and place of birth - Cénat, Jude Mary; Mistry, Shruti (Frontiers in Psychology, 2025)
IntroductionThis study used an intersectional theoretical framework to investigate the association between racial discrimination experience and life satisfaction among Black individuals aged 15 to 40 years old in Canada, exploring the mediation role of social support and the moderation role of gender and place of birth.MethodsA convenience sample of 860 participants completed questionnaires assessing life satisfaction, everyday racial discrimination, social support, and sociodemographic information.ResultsFindings showed that participants exposed to higher levels of everyday racial discrimination had the lowest scores of life satisfaction, W (3, 409) = 5.74; p < 0.001. Regression analyses showed that everyday racial discrimination negatively predicted life satisfaction (β = −0.15, p < 0.001), while social support (β = 0.38, p < 0.001) positively predicted it. Results from the mediation moderated model revealed a negative association between racial discrimination and life satisfaction (β = −0.34, p < 0.001), which was partially mediated by social support (β = 0.37, p < 0.001).ConclusionsThis research highlights the adverse effects of racism on Black individuals’ life satisfaction and underscores the role of social support in explaining these effects. Clinicians are encouraged to adopt an intersectional approach, especially for Black women and gender-diverse Black individuals who are at a higher risk of experiencing the impact of racial discrimination on life satisfaction.